Islam in der Moderne, Moderne im Islam: eine Festschrift für Reinhard Schulze zum 65. Geburtstag - Zemmin, Florian; Stephan, Johannes; Corrado, Monica (Social, economic and political studies of the Middle East, 2018)
Zusammenfassung: This Festschrift brings together a range of scholars who congratulate Reinhard Schulze on the occasion of his 65th birthday by shedding light and reflecting on the relation between Islam and modernity. Scholars from the fields of Islamic studies, religious studies, sociology and Arabic literature connect in various ways to Reinhard Schulze's work to constructively criticize a Eurocentric understanding of modernity. The more specific aspects dealt with under the overarching topic of Islam and modernity make for the four thematic parts of this volume: the study of religion, Islam, and Islamic studies; Islamic knowledge cultures and normativity; language and literature as media of modernity; Islam and Islamic studies in the public sphere--back cover
Beiträge teilweise in englischer und teilweise in deutscher Sprache. - Zusammenfassungen in englischer Sprache
Keywords: Festschrift; Sozialer Wandel; Kulturwandel; Islamische Staaten; Medien; Öffentlichkeit; Moderne; Islamwissenschaft; Kultur; Islam